Patents and the Regress of Useful Arts - Torrance, Dr. Andrew W.; Tomlinson, Dr. Bill (Science and Technology Law Review, 2009)
Patent systems are often justified by an assumption that innovation will be spurred by the prospect of patent protection, leading to the accrual of greater societal benefits than would be possible under non-patent systems. However, little empirical evidence exists to support this assumption. One way to test the hypothesis that a patent system promotes innovation is to simulate the behavior of inventors and competitors experimentally under conditions approximating patent and non-patent systems. Employing a multi-user interactive simulation of patent and non-patent (commons and open source) systems (―PatentSim‖), this study compares rates of innovation, productivity, and societal utility. PatentSim uses an abstracted and cumulative model of the invention process, a database of potential innovations, an interactive interface that allows users to invent, patent, or open source these innovations, and a network over which users may interact with one another to license, assign, buy, infringe, and enforce patents. Data generated thus far using PatentSim suggest that a system combining patent and open source protection for inventions (that is, similar to modern patent systems) generates significantly lower rates of innovation (p<0.05), productivity (p<0.001), and societal utility (p<0.002) than does a commons system. These data also indicate that there is no statistical difference in innovation, productivity, or societal utility between a pure patent system and a system combining patent and open source protection. The results of this study are inconsistent with the orthodox justification for patent systems. However, they do accord well with evidence from the increasingly important field of user and open innovation. Simulation games of the patent system could even provide a more effective means of fulfilling the Constitutional mandate “to promote the Progress of . . . useful Arts” than does the orthodox assumption that technological innovation can be encouraged through the prospect of patent protection.